Elastohydrodynamic Lubrication of Compliant Circular Contacts near Glass-Transition Temperature - Krupka, Jiri; Dockal, Krystof; Krupka, Ivan; Hartl, Martin (Lubricants, 2022)
Lubrication of polymer materials nowadays represents a subject of interest in many engineering applications, such as bearings or gears, to utilize them in the areas where conventional metal materials have so far dominated. However, material properties of polymers are strongly dependent on temperature that delimits a lubrication process and leads to manifestations of viscoelastic behavior of polymers. An understanding of mechanisms, which are responsible for formation of film thickness near the glass-transition temperature, is necessary to prevent initialization of failure modes and to increase the durability of polymer engineering components. Optical chromatic interferometry was applied to investigate development of film thickness and changes in contact geometry of compliant circular contacts operated in the elastohydrodynamic lubrication regime (EHL). Film thickness was compared with soft EHL prediction models, differences in contact geometry were assessed and their contribution to film thickness development were evaluated. Qualitatively good agreement of experimental results of central film thickness and soft EHL predictions was observed; however, minimum film thickness shows significant discrepancies. Outcomes and findings confirm the operation of the compliant circular contact in Isoviscous-elastic regime of EHL and the main influence of temperature and load to thermomechanical response of amorphous polymer PMMA.